Melanoma in Chile: demographics and clinico-pathological features - Koch Hein, Erica C.; Villanueva, Francisco; Vilbert, Maysa; Araya, Verónica; Abarzúa-Araya, Álvaro; Antúnez-Lay, Andrea; Cárdenas, Consuelo; Castro, Juan Camilo; Dominguez, Francisco; Droppelmann, Katherine; Droppelmann, Nicolás; Galindo, Héctor; et al. (Frontiers in Oncology, 2025)
BackgroundMelanoma incidence is rising globally, yet epidemiological data from Latin America remain limited. In low- and middle-income countries, such data are essential for shaping evidence-based public health strategies. ObjectivesTo describe the demographic, clinical, and pathological characteristics of melanoma in Chile using a multi-institutional registry.MethodsWe conducted a multicenter observational cohort study including patients ≥18 years with histologically confirmed melanoma diagnosed between 2014 and 2022 at one public and one private tertiary center in Santiago. Demographic, clinical, pathological, molecular, and survival data for cutaneous melanoma were analyzed using descriptive and survival statistics.ResultsA total of 1,037 patients were included, of whom 979 (94.4%) had cutaneous melanoma. Among these patients, median age was 55 years and 54.8% were female. Cutaneous melanoma was more often diagnosed at early stages, particularly in the private setting. The most frequent histopathological subtypes were superficial spreading (31.6%), nodular (17.8%), and acral lentiginous melanoma (9.3%). Self-detection was the most common mode of identification (52.8%). Among patients with stage III–IV cutaneous melanoma tested for BRAF, 47.6% were positive. Higher risk of death was associated with advanced stage, nodular or amelanotic subtypes, BRAF-mutant tumors, male sex, and age ≥65 years. Only 34.8% of patients with stage IIB–IV cutaneous melanoma received systemic therapy.ConclusionThis study offers the most comprehensive characterization of melanoma in Chile to date, underscoring survival disparities by clinical, pathological, and healthcare access factors. Findings highlight the urgent need to expand access to early detection, molecular testing, and systemic therapies.